UPAYA MENINGKATKAN KEMANDIRIAN DAN HASIL BELAJAR MATEMATIKA MELALUI WHO WANT TO BE A STAR CLASS PADA SISWA KELAS VIII A SMP NEGERI 1 ADIMULYO KABUPATEN KEBUMEN - Viva Dewi Yuliana; A. A Sujadi (UNION: Jurnal Ilmiah Pendidikan Matematika, 2015)
The objectives of this study are to describe (1)) learning process by using Who Want To Be a Star Class to improve students’ learning achievement of mathematics and (2) learning process by using Who Want To Be A Star Class to improve students’ independence in learning mathematics This study reports that (1) there was an average score improvement 63.33 in pre cycle and 67.27 in cycle with the percentage 40%. There was an average score improvement from 63.33 in cycle I and 72.8 in cycle II with the interval score between 75 – 100. Based on the results of analysis, the average score of cycle II was 74 with the percentage 66.67%. (2) Based on the results of analysis, there were 8 respondents in high category (26.67%), 8 respondents in enough category (26.67%), and 14 respondents in low category (46.66%). It could be concluded that the students’ learning independence in cycle I was in low category (46.66%). In cycle II, there were 14 respondents in high category (46.67%), 12 respondents in enough category (40%), and 4 respondents in low category (13.33%). It could be concluded that the students’ learning independence in cycle I was in high category (46.67%). It could be concluded that the students’ learning independence in cycle II was in high category (46.67%). So, successful indicator had been reached out.